Identificacion y abundancia de coleopterros coccinelidos en los cultivos de citricos valencianos - Alvis, L.=700 1 Raimundo, A.; Villalba, M.; Garcia-Mari, F.
(Es, En)
ilus., 39 ref.
Keywords: COCCINELLIDAE; DEPREDADORES; CITRUS; CONTROL BIOLOGICO; ESPAÑA